2022
DOI: 10.3389/fpls.2022.1022319
|View full text |Cite
|
Sign up to set email alerts
|

Promoting growth and production of sunchoke (Helianthus tuberosus) by co-inoculation with phosphate solubilizing bacteria and arbuscular mycorrhizal fungi under drought

Abstract: Due to different functions of phosphate solubilizing bacteria (PSB) and arbuscular mycorrhizal fungi (AMF), their potential synergistic effects on enhancing plant growth and yield are worth investigating, especially under adverse conditions. This work focused on the isolation of PSB and characterization for their plant growth promoting properties under drought. The most efficient P solubilizing bacterium was isolated and identified as Burkholderia vietnamiensis strain KKUT8-1. Then, a factorial experiment on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…AMF colonization can further enhance the level of free amino acids in the plant. AM symbiosis in Helianthus tuberosus and Sesamum indicum increased the level of free amino acids (Gholinezhad and Darvishzadeh 2021;Nacoon et al 2022). Zea mays had higher accumulation of γ-aminobutyric acid, free amino acids, arginine, and ornithine when inoculated with Rhizophagus irregularis as compared to the non-AMF plants growing in water stress conditions .…”
Section: Better Osmotic Adjustmentmentioning
confidence: 95%
“…AMF colonization can further enhance the level of free amino acids in the plant. AM symbiosis in Helianthus tuberosus and Sesamum indicum increased the level of free amino acids (Gholinezhad and Darvishzadeh 2021;Nacoon et al 2022). Zea mays had higher accumulation of γ-aminobutyric acid, free amino acids, arginine, and ornithine when inoculated with Rhizophagus irregularis as compared to the non-AMF plants growing in water stress conditions .…”
Section: Better Osmotic Adjustmentmentioning
confidence: 95%
“…Previous studies reported increased the levels of low molecular weight antioxidants in rice and enzymatic antioxidants in maize with the addition of Sb [40]. The symbiotic relationship with AMF has been consistently shown to positively affect the production of secondary compounds in plants [41]. As for previous studies [42,43] [6] who describe a clear increase in the phenolic compounds, especially the flavonoids in roots and leaves, in response to Sb toxicity and was explained by their protective effect against oxidative damage.…”
Section: Amf Application Improves the Nutritional Value Of Mays Grain...mentioning
confidence: 85%
“…B. magaterium ( ATCC 14511) was used as the positive control. The phosphate solubilizing index (PSI) was calculated as a ratio of halo diameter over colony diameter ( Nacoon et al., 2022 ). Hydrogen peroxide was used to test for catalase activity in all the isolates ( Pakpour and Horhan, 2021 ).…”
Section: Methodsmentioning
confidence: 99%